Education in Police Training: A Case Study of the European Training Platform on Domestic Violence - Sérgio, Felgueiras; Sónia M. A., Morgado (Magyar Rendészet, 2025)
The Covid-19 pandemic has significantly impacted police higher education in Portugal, necessitating a shift to web-based learning environments. This study underscores the transformative potential of digital education in improving police training using the European Training Platform on Domestic Violence as a case study. The study employs a multiple-methods approach, combining a case study analysis of the platform’s architecture, modules and features with a scoping review of the literature on digital education in police training. It draws on constructivist principles and the SCRUM framework to analyse the platform’s pedagogical approach. The analysis highlights the platform’s strengths in promoting active engagement, critical thinking and continuous professional development. It also reveals the potential of digital education to foster collaboration, knowledge sharing and proactive intervention in addressing domestic violence. This research underscores the transformative potential of digital education for police training, offering insights into how digital platforms can be leveraged to enhance professional development and improve responses to critical issues like domestic violence.